Regulation of terpenoid biosynthesis by miRNA in Persicaria minor induced by Fusarium oxysporum - Samad, Abdul Fatah A. (BMC Genomics, 2019)
BACKGROUND: Persicaria minor (kesum) is an herbaceous plant with a high level of secondary metabolite compounds, particularly terpenoids. These terpenoid compounds have well-established roles in the pharmaceutical and food industries. Although the terpenoids of P. minor have been studied thoroughly, the involvement of microRNA (miRNA) in terpenoid regulation remains poorly understood and needs to be explored. In this study, P. minor plants were inoculated with the pathogenic fungus Fusarium oxysporum for terpenoid induction. RESULT: SPME GC-MS analysis showed the highest terpenoid accumulation on the 6th day post-inoculation (dpi) compared to the other treatment time points (0 dpi, 3 dpi, and 9 dpi). Among the increased terpenoid compounds, α-cedrene, valencene and β-bisabolene were prominent. P. minor inoculated for 6 days was selected for miRNA library construction using next generation sequencing. Differential gene expression analysis showed that 58 miRNAs belonging to 30 families had significantly altered regulation. Among these 58 differentially expressed genes (DEGs), 33 miRNAs were upregulated, whereas 25 miRNAs were downregulated. Two putative novel pre-miRNAs were identified and validated through reverse transcriptase PCR. Prediction of target transcripts potentially involved in the mevalonate pathway (MVA) was carried out by psRobot software, resulting in four miRNAs: pmi-miR530, pmi-miR6173, pmi-miR6300 and a novel miRNA, pmi-Nov_13. In addition, two miRNAs, miR396a and miR398f/g, were predicted to have their target transcripts in the non-mevalonate pathway (MEP). In addition, a novel miRNA, pmi-Nov_12, was identified to have a target gene involved in green leaf volatile (GLV) biosynthesis. RT-qPCR analysis showed that pmi-miR6173, pmi-miR6300 and pmi-nov_13 were downregulated, while miR396a and miR398f/g were upregulated. Pmi-miR530 showed upregulation at 9 dpi, and dynamic expression was observed for pmi-nov_12. Pmi-6300 and pmi-miR396a cleavage sites were detected through degradome sequence analysis. Furthermore, the relationship between miRNA metabolites and mRNA metabolites was validated using correlation analysis. CONCLUSION: Our findings suggest that six studied miRNAs post-transcriptionally regulate terpenoid biosynthesis in P. minor. This regulatory behaviour of miRNAs has potential as a genetic tool to regulate terpenoid biosynthesis in P. minor. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12864-019-5954-0) contains supplementary material, which is available to authorized users.